A study of the use of mobile phones by older persons - Kurniawan, Sri; Mahmud , Murni; Nugroho, Yanuar (2006)
This paper reports on issues related to the use of mobiles phones by older people. This study uses triangulation, a mixed method of qualitative (focus group discussions) and quantitative (online questionnaire) approaches. Usage patterns, problems, perceived benefits and desired and unwanted features were covered in this study.